ФОРМУВАННЯ ПРОФЕСІЙНО-ПЕДАГОГІЧНОЇ СПРЯМОВАНОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ ЯК ОСНОВИ ЙОГО ПЕДАГОГІЧНОЇ КУЛЬТУРИ (Педагогіка вищої та середньої школи, 2022)
The author in the article determines the result of research on the problem of professional and pedagogically-oriented forming as basic part of teacher’s culture.